(untitled) (Physical Education, Health and Social Sciences, 2025)
Poverty and vulnerability in developing countries such as Pakistan is a problem, despite the growth of the social protection systems across the world. Cash transfer programs like the Benazir Income Support Programme (BISP) and the Ehsaas program have been implemented to reduce poverty and provide vulnerable households with protection against economic shocks, but it is still not clear how effective they are in making households resilient in the long-term beyond consumption support. This paper will investigate how BISP and Ehsaas programs affect household resilience in Punjab, Pakistan, particularly in economic stability, consumption smoothing, income security, asset accumulation, adaptive capacity and coping mechanisms. The research also compares the results of resilience of beneficiary and non-beneficiary households in the provinces rural and urban areas. The quantitative cross-sectional research design was used to provide the objective measurement and test the relationships between variables statistically. The target population included the households in Punjab with both the beneficiaries and the non-beneficiaries of the program, where the respondents were the household heads or adult members as they would be knowledgeable about financial decisions and coping mechanisms. Cochran formula of large population was used to determine the sample size which gave an estimate of 384 respondents; they were however reduced to 350 respondents due to feasibility and time constraints. The sample size of over 300 can be said to be enough to conduct multivariate statistical analysis, which is reliable and can be generalized. Structured questionnaire was used to collect primary data with five point Likert scale, and SPSS was used to analyze the data. The descriptive statistics (frequencies, percentages, means, and standard deviations) were used to describe the major variables, and inferential statistics, especially Chi-Square test of independence, were applied to identify the relationship between program participation and household resiliency outcomes. Its findings have revealed that BISP/Ehsaas program has a significant relationship with better economic stability, increased consumption smoothing, increased asset accumulation, and higher adaptive coping capacity. The resilience outcomes were higher in beneficiary households than in non-beneficiaries, and statistical comparisons revealed that there were significant relationships between program participation and resilience dimensions (p <.05). Even though the findings emphasize the protective and promotive value of social protection programs in enhancing the resiliency of households, a fraction of households still face vulnerability, which implies the necessity to change the policies. This research makes its contribution to the empirical literature on the social protection and resilience under developing conditions and offers policy-relevant implications to enhance the strategies of poverty alleviation in Pakistan.